1991
DOI: 10.1002/1098-108x(199101)10:1<101::aid-eat2260100111>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Insight into illness and outcome in anorexia nervosa

Abstract: Thirty female subjects were followed up an average of 4.6 years after being hospitalized for anorexia nervosa. Insight into illness, symptoms, and treatment was rated for index hospitalization and assessed at follow up using the Schedule for Assessment of Insight. In addition, subjects were interviewed and assessed for level of function, symptoms of eating disorders, and the presence of significant psychopathology. The Insight Rating at index hospitalization was correlated with the Global Insight Score at foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
16
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 14 publications
(8 reference statements)
6
16
0
3
Order By: Relevance
“…The finding of a high prevalence of lifetime major depression is in accord with other studies that used structured interviews (43,44) and with those that also used a control group (28,29,45). In these studies, lifetime prevalences of major depression ranged from 40% to 100%.…”
Section: Psychiatric Diagnostic Comorbiditysupporting
confidence: 93%
“…The finding of a high prevalence of lifetime major depression is in accord with other studies that used structured interviews (43,44) and with those that also used a control group (28,29,45). In these studies, lifetime prevalences of major depression ranged from 40% to 100%.…”
Section: Psychiatric Diagnostic Comorbiditysupporting
confidence: 93%
“…71 Importantly, one early study reported that insight into illness is associated with improved treatment outcomes in AN, and that insight can increase as a function of treatment. 72 This study, in concert with the motivation literature, suggests that to the extent that denial keeps patients from seeking or engaging in treatment, it needs to be viewed as an important clinical variable, and warrants additional study. 37 Notably, there is a substantial literature that addresses a phenomenologic variant of AN in which criterion B (''Intense fear of gaining weight or becoming fat, even though underweight'' 12 ) is absent.…”
Section: Outcomesupporting
confidence: 84%
“…This is in line with a previous prospective study showing that insight remains consistent over time in patients with AN (Greenfeld et al 1991). A positive association was found between the level of insight and BMI in the total sample.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have used denial subscales of clinical instruments to investigate possible associations between insight and outcome or other clinical aspects of EDs (Morgan & Russell, 1975 ;Casper et al 1979 ;Goldberg et al 1979 ;Halmi et al 1979 ;Eckert et al 1982 ;Steinhausen, 1986 ;Casper & Heller, 1991 ;Sunday et al 1995 ;Saccomani et al 1998 ;Bizeul et al 2001). Only one study has assessed insight in patients with AN through a structured interview previously used in patients with psychosis, and found that higher levels of insight were associated with better long-term outcome measures (Greenfeld et al 1991).…”
Section: Introductionmentioning
confidence: 99%